An Overview on the Conservative Management of Endometriosis from a Naturopathic Perspective: Phytochemicals and Medicinal Plants - Balan Andreea; Moga Marius Alexandru; Dima Lorena; Dinu Catalina Georgeta; Martinescu Carmen Constantina; Panait Diana Elena; Irimie Claudia Alexandrina; Anastasiu Costin Vlad (Plants, 2021)
Background: Endometriosis is a chronic and debilitating disease, which affects millions of young women worldwide. Although medicine has incontestably evolved in the last years, there is no common ground regarding the early and accurate diagnosis of this condition, its pathogenic mechanisms, and curative treatment. Even though the spontaneous resolution of endometriosis is sometimes possible, recent reports suggested that it can be a progressive condition. It can associate chronic pelvic pain, vaginal bleeding, infertility, or malignant degenerescence. Conventional treatments could produce many side effects, and despite treatment, the symptoms may reappear. In recent years, experimental evidence suggested that plant-based medicine could exert beneficial effects on endometriosis and endometriosis-related symptoms. This study aims to highlight the pharmaceutical activity of phytochemicals and medicinal plants against endometriosis and to provide a source of information regarding the alternative treatment of this condition. Methods: For this review, we performed a research using PubMed, GoogleScholar, and CrossRef databases. We selected the articles published between January 2000 and July 2020, written in English. Results: We found 17 medicinal plants and 13 phytochemicals, which have demonstrated their beneficial effects against endometriosis. Several of their biological activities consist of antiangiogenic, anti-inflammatory effects, and oxidative-stress reduction. Conclusion: Medicinal herbs and their bioactive compounds exhibit antiangiogenic, antioxidant, sedative and pain-alleviating properties and the effects recorded until now encourage their use for the conservative management of endometriosis.
Keywords: endometriosis; traditional Chinese Medicine; medicinal herbs; nutraceuticals; phytochemicals